Sovereign credit ratings and macroeconomic variables: An application of bounds testing approach to Malaysia - Masih, Mansur; Ahmad, Abd Halim @ Hamilton; Mohd Daud, Siti Nurazira; Marzuki, Ainulashikin (IABE, 2008)
This paper aims to investigate the short- and long-run macroeconomic determinants of sovereign credit ratings in developing countries.Malaysia is used as a case study.This study employed quarterly data from 1991 to 2004.We apply a recently developed time series technique called ‘Auto-Regressive Distributed Lag’ (ARDL) [Pesaran, Shin, and Smith,Journal of Applied Econometrics, 2001] which has taken care of a major limitation of the conventional cointegrating tests in that they suffer from the pre-test biases.Based on the above rigorous methodology, our evidence tends to suggest that both in the short-and long- run, Debt ratios such as (Debt to GDP, Debt Service to Reserve) and US Treasury Bill rate (3-months) appear to have had a significant impact on Malaysia’s sovereign credit ratings.The findings of the study tend to indicate that Malaysia’s short- and long-term ability to pay its debt contain information for the prediction of her credit ratings.These findings are plausible and have strong policy implications for developing countries like Malaysia.